Recent Insights Into the Role of Autoimmunity in Idiopathic Dilated Cardiomyopathy - LAPPÉ, JASON M. (2008)
Dilated cardiomyopathy is a devastating disease associated with poor outcomes. Although the etiology of this disease remains largely unknown, so-called “idiopathic” dilated cardiomyopathy (iDCM) is associated with evidence of an autoimmune process that may be contributing to the pathophysiology of this disease. Indeed, iDCM shares many characteristics with other autoimmune diseases, including an association with systemic and organ-specific inflammation, an association with viral infections, a genetic predisposition, and a correlation with specific human leukocyte antigen subtypes. Additionally, numerous pathologic cardiac-specific autoantibodies have been associated with iDCM, including those against α-myosin, the β(1)-adrenoceptor, and cardiac troponin I. This review highlights the emerging evidence regarding autoimmune characteristics of iDCM, and summarizes the data of specific immunomodulatory therapies used to target autoimmune mechanisms in the treatment of patients with this devastating disease.